Peran Putusan Sela dan Putusan Akhir dalam Mewujudkan Keadilan Prosedural di Pengadilan - Podomi, Prayogi Aryovandri; Moonti, Roy Marthen; Ahmad, Ibrahim (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Interlocutory decisions and final decisions are two forms of court decisions that have strategic functions in ensuring the application of the principles of procedural justice. In Indonesian judicial practice, procedural irregularities, norm inconsistencies, and lack of transparency often occur which hinder the achievement of legal justice. This research aims to analyze the role and position of interlocutory decisions and final decisions in the Indonesian judicial system, and identify normative and practical obstacles faced in their implementation. The type of research used is normative juridical with conceptual and statutory approaches. The results showed that regulatory weaknesses, low quality of judicial consideration, and limited access to information were the main obstacles in realizing procedural justice. Therefore, it is recommended to harmonize procedural laws, increase the capacity of judges, and digitize open decisions to ensure effective, transparent, and dignified justice in the national justice system.